2010
DOI: 10.1159/000290775
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Trichloroethylene Hypersensitivity Syndrome with Human Herpesvirus-6 and Cytomegalovirus Reactivation

Abstract: Patients having a generalised rash with severe liver dysfunction associated with exposure to trichloroethylene (TCE) have been reported mainly in Asian countries. However, no case has been reported in Japan since the 1990s. Here, we describe a case of hypersensitivity syndrome (HS) caused by TCE in a 30-year-old Japanese man. The patient developed a rash, fever and liver dysfunction 21 days after he had been exposed to TCE at his workplace. Serum human herpesvirus (HHV)-6 and cytomegalovirus (CMV) DNA were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…Occupational TCE exposure is declining in industrialized countries because of technological innovation and legislation 1) , but it is increasing in emerging industrialized countries, especially in Asia 2) . Recently, occupational exposure to TCE was associated with severe hypersensitive skin damage and impaired hepatic function 3,4) , which has become one of the critical occupational health issues in Asia 5,6) . In the past 10 yr, an increasing number of cases suffering from TCE-induced hypersensitivity dermatitis (THD) have been reported in Guangdong Province in southern China 3) .…”
mentioning
confidence: 99%
“…Occupational TCE exposure is declining in industrialized countries because of technological innovation and legislation 1) , but it is increasing in emerging industrialized countries, especially in Asia 2) . Recently, occupational exposure to TCE was associated with severe hypersensitive skin damage and impaired hepatic function 3,4) , which has become one of the critical occupational health issues in Asia 5,6) . In the past 10 yr, an increasing number of cases suffering from TCE-induced hypersensitivity dermatitis (THD) have been reported in Guangdong Province in southern China 3) .…”
mentioning
confidence: 99%
“…In fact, we found that patch testing was negative for TCE itself, but positive for trichloroethanol, trichloroacetic acid and chloral hydrate in our patient. 7 Similarly, Phoon et al 19 observed a negative reaction for TCE itself. Conversely, three reported cases were positive for TCE on patch testing, and one of these patients was also positive for the metabolite trichloroethanol, but not for trichloroacetic acid (Table 2).…”
Section: Results Of Patch Testingmentioning
confidence: 94%
“…1,7 Lymphadenopathy is seen in 81% of TCE-related HS and 75% of DIHS. 1,7 Eosinophilia has been reported in 25% of TCE-induced HS and 70% of DIHS, 1,7 although remarkable eosinophilia was seen in the two recent Japanese cases and has been reported in other cases of TCE-induced HS. 5,7 Perhaps if physicians examined the differential count more closely during the course of the disease in reported cases the percentage of eosinophilia in TCE-induced HS may be higher.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…At present, biomarker researches about OMLDT mainly focused on three aspects: gene polymorphism [3][4][5][6][7], serum proteomics [8][9][10][11][12] and TCE metabolites [13]. Haishan Li, et al [3] identified genetic susceptible biomarkers associated with OMLDT in genes located in the human leukocyte antigen (HLA) region.…”
Section: Introductionmentioning
confidence: 99%
“…Haishan Li, et al [3] identified genetic susceptible biomarkers associated with OMLDT in genes located in the human leukocyte antigen (HLA) region. Further research [4] had illustrated that HLA-B*13:01 was also identified in the patient of Japan. Later, they not only validated the association between HLA-B*13:01 allele and OMLDT, but also identified two new loci for the disease, one was on intron of the major histocompatibility complex class I chain related gene A (MICA), and another was between HLA-B and MICA, suggesting MICA was an important gene for the disease risk in addition to HLA-B*13:01.…”
Section: Introductionmentioning
confidence: 99%